2021
DOI: 10.1111/rec.13336
|View full text |Cite
|
Sign up to set email alerts
|

Hidden variation: cultivars and wild plants differ in trait variation with surprising root trait outcomes

Abstract: Restoration practitioners have many seed material choices when restoring plant communities, and cultivars may be the most affordable and accessible material available for some species. However, the process of plant selection and commercial seed production can limit trait variability critical to survival and persistence in heterogeneous environments. Several studies show the impacts of plant selection and commercial production on trait values and variation in aboveground traits. Yet, researchers rarely assess i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…The diversity of hydrolysable monomers detected in the soybean root suberin that was purified using the ionic liquid catalyst is depicted in Figure 2 . The observed diversity of monomers is, in general, consistent to that reported before for suberin isolated from soybean roots using conventional extraction methods ( Ghanati et al, 2005 ; Thomas et al, 2007 ), notwithstanding that root traits (including suberin composition) may differ in different cultivars ( Figueroa-Bustos et al, 2020 ; Foxx and Kramer, 2021 ). Accordingly, the alka(e)noic acids (>80%) were the most abundant class of hydrolysable monomers detected, mostly hexadecanoic acid (it accounts for nearly 46% of the total monomeric content).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The diversity of hydrolysable monomers detected in the soybean root suberin that was purified using the ionic liquid catalyst is depicted in Figure 2 . The observed diversity of monomers is, in general, consistent to that reported before for suberin isolated from soybean roots using conventional extraction methods ( Ghanati et al, 2005 ; Thomas et al, 2007 ), notwithstanding that root traits (including suberin composition) may differ in different cultivars ( Figueroa-Bustos et al, 2020 ; Foxx and Kramer, 2021 ). Accordingly, the alka(e)noic acids (>80%) were the most abundant class of hydrolysable monomers detected, mostly hexadecanoic acid (it accounts for nearly 46% of the total monomeric content).…”
Section: Resultssupporting
confidence: 89%
“…The low abundance of aromatic features in the soybean root suberin–extracted suberin and in planta suberin–is likely explained by the specificity of the used cultivar. In fact, it has been reported that different cultivars have differences not only in response to drought and pathogens but also in root architecture and traits ( Figueroa-Bustos et al, 2020 ; Foxx and Kramer, 2021 ). For example, the root epidermal wall compositions of cv.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, potential negative impacts of using cultivars raise additional concerns about their ubiquitous use in restoration. Studies have found that the process by which native materials are selected and produced may result in unintentional selection for nonadaptive traits (Espeland et al 2017) or lower variability in traits (Foxx & Kramer 2020). In addition, their introduction into sites with conspecifics may negatively affect the genetic integrity of local populations (Hufford & Mazer 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Various and sometimes surprising traits have been related to plant performance in restoration settings using trait‐based methods. For example, working with the perennial grass Elymus elymoides , Kulpa and Leger (2013) found that small plants with small seeds and early phenology had high rates of survival in restored areas of the Great Basin and Foxx and Kramer (2020) found E. elymoides individuals with high root tip numbers to be effective competitors with the invasive grass Bromus tectorum . Similarly, Leger and Baughman (2015) identified early phenology, small plant size, and high root allocation to be strong predictors of plant performance across 420 seeding treatments implemented throughout the western United States (US hereafter).…”
Section: Introductionmentioning
confidence: 99%
“…The previous interaction environment also produced a different relationship between the focal plant and non-focal neighbor’s leaf production indicating that interspecific-induced and intraspecific-induced plants differed in responses to trait hierarchy with the new neighbors. Trait hierarchies are often explored between species 33 , 42 , however trait differences exist below the species level 34 , 44 , 45 and influence coexistence 46 . For example, Abbott and Stachowicz 46 showed that increasing root mass distance in pairwise competing genotypes of eelgrass ( Zostera marina ) decreased the probability of genotype coexistence.…”
Section: Discussionmentioning
confidence: 99%